The Relationship Between Physical Activity and Dietary Patterns and the Prevalence of Obesity Among Adolescents - Fatma Syukrina; Rizki Rahma Wati (Nindikayla Institute, 2025)
Adolescent obesity is a global health issue that requires serious attention. This study aims to describe the relationship between physical activity and dietary patterns and the prevalence of obesity among adolescents. The method used was a qualitative case study with a descriptive approach. Data were collected through in-depth interviews, observations, and anthropometric measurements. The results indicate that adolescents with low physical activity levels are more likely to be obese, while high-calorie, low-fiber diets also contribute to weight gain. The family environment, school, peers, and social media also play a significant role in shaping adolescents’ eating behaviors and physical activity. The conclusion of this study is that low physical activity and unhealthy dietary patterns are the primary risk factors for obesity in adolescents. Efforts to prevent obesity must involve increasing physical activity, promoting a balanced diet, providing nutrition education, and fostering a supportive environment